Visão de um estudante sobre a formação médica na UFCar: uma narrativa crítica-reflexiva - Machado, Gabriele Vitoria Gerciano (Universidade Federal de São Carlos, 2024)
This Course Completion Work (TCC) presents a reflection on the academic trajectory from a student's personal point of view. To this end, the university admission process is presented chronologically, such as the Political Pedagogical Project of the course is structured and an overview of the experiences experienced in the three educational cycles. The constructivist approach of the course helped to improve learning and guided the student to a practical patient-centered clinic, promoting empathy, responsibility and respect in the doctor-patient relationship. The COVID-19 pandemic had a significant impact on training, bringing academic and personal losses that required a lot of effort and work to alleviate them. It is concluded, therefore, that the constructivist methodology, even though far from perfect, provides valuable tools to students to deal with adversity and promotes longitudinal knowledge practical, theoretical and attitudinal.
A student's view of medical training at UFSCar: a critical-narrative reflective
Keywords: Autorreflexão; Self-reflection; Metodologia ativa; Espiral construtivista; Narrativa reflexiva; Medicina; Relato de experiência; Educação médica; Active methodology; Constructivist spiral; Reflective narrative; Medicine; Experience report; Medical education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM